Infants' discrimination of consonant contrasts in the presence and absence of talker variability. (16th October 2020) - Quam, Carolyn; Clough, Lauren; Knight, Sara; Gerken, LouAnn
Abstract: To learn speech‐sound categories, infants must identify the acoustic dimensions that differentiate categories and selectively attend to them as opposed to irrelevant dimensions. Variability on irrelevant acoustic dimensions can aid formation of robust categories in infants through adults in tasks such as word learning (e.g., Rost and McMurray, 2009) or speech‐sound learning (e.g., Lively et al., 1993). At the same time, variability sometimes overwhelms learners, interfering with learning and processing. Two prior studies (Kuhl & Miller, 1982; Jusczyk, Pisoni, & Mullennix, 1992) found that irrelevant variability sometimes impaired early sound discrimination. We asked whether variability would impair or facilitate discrimination for older infants, comparing 7.5‐month‐old infants' discrimination of an early acquired native contrast, /p/ vs. /b/ (in the word forms /pIm/ vs. /bIm/), in Experiment 1, with an acoustically subtle, non‐native contrast, /n/ vs. /ŋ/ (in /nIm/ vs. /ŋIm/), in Experiment 2. Words were spoken by one or four talkers. Infants discriminated the native but not the non‐native contrast, and there were no significant effects of talker condition. We discuss implications for theories of phonological learning and avenues for future research.